ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA GAMBAR PADA PEMBELAJARAN IPA MELALUI ADOBE FLASH - Ghoni, Abdul (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2020)
Abstract: This study aims to determine the level of development needs of media images in learning science through Adobe Flash in MI Maarif Mangunsari Salatiga. A good learning media certainly has to go through the stages of research as well as this research which uses descriptive analysis research method that is by distributing questionnaires filled by 6 teachers at MI Maarif Mangunsari Salatiga City which contains statements about the need for media development. The results of this study is: Development of image media in science learning through Adobe Flash material of the human digestive system is very much needed for students and teachers in MI Maarif Mangunsari, Sidomukti Subdistrict, Salatiga City. Keywords: Development of media, Adobe Flash and the human digestive system.